Delivery of Antisense Oligonucleotides Mediated by a Hydrogel System: In Vitro and In Vivo Application in the Context of Spinal Cord Injur - Moreno, PMD (2019)
Biomaterials-based hydrogels are attractive drug-eluting vehicles in the context of RNA therapeutics, such as those utilizing antisense oligonucleotide or RNA interference based drugs, as they can potentially reduce systemic toxicity and enhance in vivo efficacy by increasing in situ concentrations. Here we describe the preparation of antisense oligonucleotide-loaded fibrin hydrogels exploring their applications in the context of the nervous system utilizing an organotypic dorsal root ganglion explant in vitro system and an in vivo model of spinal cord injury.